Modified plastic master batch and preparation method thereof

By adding modified lignin fibers, sepiolite fibers and modified glass fibers to the plastic masterbatches to form a crosslinked structure and a stable carbon layer, the problem of insufficient flame retardant performance of existing plastic masterbatches at high temperatures is solved. Achieve better flame arrest and material stability.

CN119286102AInactive Publication Date: 2025-01-10YANTAI LIANGCAI PLASTIC TECH CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411832790.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-01-10
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing plastic masterbatches have shortcomings in flame retardant properties, making it difficult to effectively prevent flame propagation and material disintegration at high temperatures.

Method used

By adding modified lignin fibers, sepiolite fibers and modified glass fibers, a cross-linked structure and a stable carbon layer are formed to improve flame retardant performance, and improve flame retardant from three dimensions: gas flame retardant, heat absorption and structural stability. sex.

Benefits of technology

It significantly improves the flame retardant performance of plastic masterbatches, can effectively prevent flame propagation at high temperatures, reduce overall temperature, and maintain the stability of the material, prevent disintegration.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to a modified plastic master batch and a preparation method thereof, and belongs to the technical field of plastic master batches. The modified plastic master batch disclosed by the invention is prepared from the following raw materials: carrier resin, sepiolite fibers, modified lignin fibers and modified glass fibers. Melamine is used for modifying the lignin fiber, a formed cross-linked structure improves the thermal stability and mechanical strength of lignin, meanwhile, the nitrogen content of the lignin fiber is greatly increased, and therefore the flame retardant effect of the modified lignin fiber is enhanced; by matching with the sepiolite fiber, a large amount of heat can be absorbed, so that the overall temperature is reduced; in addition, the modified glass fibers are added, so that the modified glass fibers have incombustibility, a formed framework is kept stable at high temperature, and disintegration of the material is prevented. Therefore, the modified lignin fibers, the sepiolite fibers and the modified glass fibers improve the flame retardance of the modified master batch from three dimensions of gas flame retardance, heat absorption and framework stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of plastic masterbatches and relates to a modified plastic masterbatch and a preparation method thereof. Background Art

[0002] Masterbatch is the full name of plastic masterbatch, also known as masterbatch. It is a plastic processing aid developed in the 1980s. It is composed of chemical additives, carrier resins and dispersants. Plastic masterbatch is widely used in the production process of various plastic products. By adding an appropriate amount of masterbatch, the production process can be simplified, the production efficiency can be improved, and the performance of the product can be improved. For example, defoaming masterbatch improves the physical and mechanical properties of the product while saving energy and cost. In addition, plastic masterbatch can also be used to manufacture various functional plastic products, such as flame retardant products.

[0003] Lignin is a green renewable resource with abundant reserves in nature. Together with cellulose and hemicellulose, it constitutes the basic skeleton of plants and is the most abundant and important natural polymer substance after cellulose in quantity. Lignin is mainly composed of three chemical elements: carbon, hydrogen, and oxygen. The most important structural unit is the benzene ring, which contains a large number of phenolic hydroxyl functional groups on the benzene ring and the straight chain. These characteristics meet the requirements of flame retardants that are rich in carbon elements and hydroxyl groups. Therefore, lignin is feasible to replace traditional intumescent flame retardants and has broad application prospects in flame retardant materials.

[0004] Therefore, the present application proposes a modified plastic masterbatch and a preparation method thereof, and further improves the flame retardant properties of the plastic masterbatch by adding modified lignin fiber material to the carrier resin of the plastic masterbatch body. Summary of the invention

[0005] The modified plastic masterbatch disclosed in the present invention improves the flame retardancy of the modified masterbatch from three dimensions: gas flame retardancy, heat absorption and structural stability by adding modified lignin fiber, sepiolite fiber and modified glass fiber.

[0006] The purpose of the present invention can be achieved through the following technical solutions: A modified plastic masterbatch, the modified plastic masterbatch comprising the following raw materials: carrier resin, sepiolite fiber, modified lignin fiber and modified glass fiber, wherein the carrier resin is composed of polyethylene, random polypropylene and polypropylene in a mass ratio of 1:1-2:1-3, and the preparation method of the modified lignin fiber comprises the following steps: (1) dissolving lignin in an alkaline solution, then adding formaldehyde and mixing, and then heating to obtain a mixture; (2) Add melamine to the mixture and keep it warm, then add dilute hydrochloric acid and stir, let it stand to form a precipitate, filter it, wash the solid with distilled water, and dry it to obtain the modified lignin fiber.

[0007] Furthermore, in the step (1), the ratio of lignin, alkaline solution and formaldehyde is 4-6g:100-150mL:2-5mL, wherein the alkaline solution refers to a sodium hydroxide solution with a mass fraction of 1-5%, and the heating time and temperature are 1-2h and 70-80°C, respectively.

[0008] Furthermore, in step (2), the ratio of the mixture, melamine and dilute hydrochloric acid is 150-180 mL: 2-6 g: 10-15 mL, wherein the mass fraction of the dilute hydrochloric acid is 35-38%, and the drying time and temperature are 1-2 h and 80-100° C., respectively.

[0009] Furthermore, the preparation method of the modified glass fiber is: glass fiber is mixed with anhydrous ethanol and ultrasonically treated, vinyl triethoxysilane is added, heated and stirred, and then cooled to room temperature, centrifuged to obtain a solid, and vacuum dried to obtain the modified glass fiber.

[0010] Furthermore, the ratio of the glass fiber, anhydrous ethanol and vinyl triethoxysilane is 10-15g:100-120mL:2-5g, the ultrasonic treatment time is 20-30min, the heating refers to heating to 50-60°C, and the vacuum drying time and temperature are 30-40min and 70-80°C respectively.

[0011] A method for preparing a modified plastic masterbatch, the method comprising the following steps: A1: Add the carrier resin into a high-speed mixer, heat it, and mix it at high speed to form a mixture a; A2: The modified lignin fiber is added to anhydrous ethanol and ultrasonically treated, and then added to a high-speed mixer, and sepiolite fiber and modified glass fiber are continuously added to the high-speed mixer and heated and stirred to obtain a mixture b; A3: Add mixed material a and mixed material b into a twin-screw extruder for blending and extrusion, pelletize, and dry to obtain a modified plastic masterbatch.

[0012] Furthermore, in the step A1, the heating temperature and time are 260-270° C. and 10-12 min, respectively, and the rotation speed of the high-speed mixing is 1800-2000 r / min.

[0013] Furthermore, in step A2, the ratio of modified lignin fiber, anhydrous ethanol, sepiolite fiber and modified glass fiber is 10-15g:50-70mL:5-7g:5-8g, the ultrasonic treatment time is 8-12min, the heating refers to heating to 210-220°C, and the stirring time is 12-13min.

[0014] Furthermore, in step A3, the mass ratio of mixture a to mixture b is 150-180:30-45, and the drying temperature is 70-80°C.

[0015] Beneficial effects of the present invention: The present invention uses melamine to modify lignin fiber, and the formed cross-linked structure improves the thermal stability and mechanical strength of lignin, and at the same time greatly increases the nitrogen content of the lignin fiber, and can form a stable carbon layer at high temperature. At the same time, the generation of nitrogen has a dual effect of preventing the spread of flames and enhancing the flame retardant effect of the modified lignin fiber; The present invention can form a stable carbon layer at high temperature. At the same time, the modified lignin fiber generated by nitrogen and the sepiolite fiber can absorb a large amount of heat, thereby reducing the overall temperature. In addition, the addition of modified glass fiber itself is non-flammable, and the formed skeleton remains stable at high temperature, preventing the disintegration of the material. Therefore, the modified lignin fiber, sepiolite fiber and modified glass fiber improve the flame retardancy of the modified masterbatch from three dimensions: gas flame retardancy, heat absorption and structural stability. DETAILED DESCRIPTION

[0016] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with embodiments.

[0017] The polyethylene in all the embodiments and comparative examples of the present invention was purchased from Korea Petrochemical, the random polypropylene was purchased from Yanshan Petrochemical, the polypropylene was purchased from Shengfeng, the lignin fiber was purchased from Xinyuan New Materials, and the glass fiber was purchased from Tonghui.

[0018] Embodiment 1: A modified plastic masterbatch, the modified plastic masterbatch comprising the following raw materials: carrier resin, sepiolite fiber, modified lignin fiber and modified glass fiber, wherein the carrier resin is composed of polyethylene, random polypropylene and polypropylene in a mass ratio of 1:1:1, and the preparation method of the modified lignin fiber comprises the following steps: (1) dissolving lignin in an alkaline solution, then adding formaldehyde and mixing, and then heating to obtain a mixture; (2) Add melamine to the mixture and keep it warm, then add dilute hydrochloric acid and stir, let it stand to form a precipitate, filter it, wash the solid with distilled water, and dry it to obtain the modified lignin fiber.

[0019] In the step (1), the ratio of lignin, alkaline solution and formaldehyde is 4g:100mL:2mL, wherein the alkaline solution refers to a sodium hydroxide solution with a mass fraction of 1%, and the heating refers to heating to a temperature of 70°C.

[0020] In the step (2), the ratio of the mixture, melamine and dilute hydrochloric acid is 150 mL:2 g:10 mL, wherein the mass fraction of the dilute hydrochloric acid is 35%, and the drying time and temperature are 1 h and 80° C., respectively.

[0021] The preparation method of the modified glass fiber is as follows: glass fiber is mixed with anhydrous ethanol and subjected to ultrasonic treatment, vinyl triethoxysilane is added, the mixture is heated and stirred, and then cooled to room temperature, centrifuged to obtain a solid, and vacuum dried to obtain the modified glass fiber.

[0022] The ratio of the glass fiber, anhydrous ethanol and vinyl triethoxysilane is 10g:100mL:2g, the ultrasonic treatment time is 20min, the heating time and temperature are 20min and 50°C respectively, and the vacuum drying time and temperature are 30min and 70°C respectively.

[0023] A method for preparing a modified plastic masterbatch, the method comprising the following steps: A1: Add the carrier resin into a high-speed mixer, heat it, and mix it at high speed to form a mixture a; A2: The modified lignin fiber is added to anhydrous ethanol and ultrasonically treated, and then added to a high-speed mixer, and sepiolite fiber and modified glass fiber are continuously added to the high-speed mixer and heated and stirred to obtain a mixture b; A3: Add mixed material a and mixed material b into a twin-screw extruder for blending and extrusion, pelletize, and dry to obtain a modified plastic masterbatch.

[0024] The heating temperature and time in step A1 are 260° C. and 10 min respectively, and the rotation speed of the high-speed mixing is 1800 r / min.

[0025] In the step A2, the ratio of modified lignin fiber, anhydrous ethanol, sepiolite fiber and modified glass fiber is 10g:50mL:5g:5g, the ultrasonic treatment time is 8min, the heating refers to heating to 210°C, and the stirring time is 12min.

[0026] In the step A3, the mass ratio of mixture a to mixture b is 150:30, and the drying temperature is 70°C.

[0027] Embodiment 2: A modified plastic masterbatch, the modified plastic masterbatch comprising the following raw materials: carrier resin, sepiolite fiber, modified lignin fiber and modified glass fiber, wherein the carrier resin is composed of polyethylene, random polypropylene and polypropylene in a mass ratio of 1:1.5:2, and the preparation method of the modified lignin fiber comprises the following steps: (1) dissolving lignin in an alkaline solution, then adding formaldehyde and mixing, and then heating to obtain a mixture; (2) Add melamine to the mixture and keep it warm, then add dilute hydrochloric acid and stir, let it stand to form a precipitate, filter it, wash the solid with distilled water, and dry it to obtain the modified lignin fiber.

[0028] In the step (1), the ratio of lignin, alkaline solution and formaldehyde is 5g:125mL:3.5mL, wherein the alkaline solution refers to a sodium hydroxide solution with a mass fraction of 3%, and the heating refers to heating to 75°C.

[0029] In the step (2), the ratio of the mixture, melamine and dilute hydrochloric acid is 165 mL:4 g:12 mL, wherein the mass fraction of the dilute hydrochloric acid is 37%, and the drying time and temperature are 1.5 h and 90° C., respectively.

[0030] The preparation method of the modified glass fiber is as follows: glass fiber is mixed with anhydrous ethanol and subjected to ultrasonic treatment, vinyl triethoxysilane is added, the mixture is heated and stirred, and then cooled to room temperature, centrifuged to obtain a solid, and vacuum dried to obtain the modified glass fiber.

[0031] The ratio of the glass fiber, anhydrous ethanol and vinyl triethoxysilane is 13g:110mL:4g, the ultrasonic treatment time is 25min, the heating time and temperature are 25min and 55°C respectively, and the vacuum drying time and temperature are 35min and 75°C respectively.

[0032] A method for preparing a modified plastic masterbatch, the method comprising the following steps: A1: Add the carrier resin into a high-speed mixer, heat it, and mix it at high speed to form a mixture a; A2: The modified lignin fiber is added to anhydrous ethanol and ultrasonically treated, and then added to a high-speed mixer, and sepiolite fiber and modified glass fiber are continuously added to the high-speed mixer and heated and stirred to obtain a mixture b; A3: Add mixed material a and mixed material b into a twin-screw extruder for blending and extrusion, pelletize, and dry to obtain a modified plastic masterbatch.

[0033] The heating temperature and time in step A1 are 265° C. and 11 min respectively, and the rotation speed of the high-speed mixing is 1900 r / min.

[0034] In the step A2, the ratio of modified lignin fiber, anhydrous ethanol, sepiolite fiber and modified glass fiber is 13g:60mL:6g:6g, the ultrasonic treatment time is 10min, the heating refers to heating to 215°C, and the stirring time is 12min.

[0035] In the step A3, the mass ratio of mixture a to mixture b is 165:38, and the drying temperature is 75°C.

[0036] Embodiment 3: A modified plastic masterbatch, the modified plastic masterbatch comprising the following raw materials: carrier resin, sepiolite fiber, modified lignin fiber and modified glass fiber, wherein the carrier resin is composed of polyethylene, random polypropylene and polypropylene in a mass ratio of 1:2:3, and the preparation method of the modified lignin fiber comprises the following steps: (1) dissolving lignin in an alkaline solution, then adding formaldehyde and mixing, and then heating to obtain a mixture; (2) Add melamine to the mixture and keep it warm, then add dilute hydrochloric acid and stir, let it stand to form a precipitate, filter it, wash the solid with distilled water, and dry it to obtain the modified lignin fiber.

[0037] In the step (1), the ratio of lignin, alkaline solution and formaldehyde is 6g:150mL:5mL, wherein the alkaline solution refers to a sodium hydroxide solution with a mass fraction of 5%, and the heating refers to heating to 80°C.

[0038] In the step (2), the ratio of the mixture, melamine and dilute hydrochloric acid is 180 mL:6 g:15 mL, wherein the mass fraction of the dilute hydrochloric acid is 38%, and the drying time and temperature are 2 h and 100° C., respectively.

[0039] The preparation method of the modified glass fiber is as follows: glass fiber is mixed with anhydrous ethanol and subjected to ultrasonic treatment, vinyl triethoxysilane is added, the mixture is heated and stirred, and then cooled to room temperature, centrifuged to obtain a solid, and vacuum dried to obtain the modified glass fiber.

[0040] The ratio of the glass fiber, anhydrous ethanol and vinyl triethoxysilane is 15g:120mL:5g, the ultrasonic treatment time is 30min, the heating time and temperature are 30min and 60°C respectively, and the vacuum drying time and temperature are 40min and 80°C respectively.

[0041] A method for preparing a modified plastic masterbatch, the method comprising the following steps: A1: Add the carrier resin into a high-speed mixer, heat it, and mix it at high speed to form a mixture a; A2: The modified lignin fiber is added to anhydrous ethanol and ultrasonically treated, and then added to a high-speed mixer, and sepiolite fiber and modified glass fiber are continuously added to the high-speed mixer and heated and stirred to obtain a mixture b; A3: Add mixed material a and mixed material b into a twin-screw extruder for blending and extrusion, pelletize, and dry to obtain a modified plastic masterbatch.

[0042] The heating temperature and time in step A1 are 270° C. and 12 min respectively, and the rotation speed of the high-speed mixing is 2000 r / min.

[0043] In the step A2, the ratio of modified lignin fiber, anhydrous ethanol, sepiolite fiber and modified glass fiber is 15g:70mL:7g:8g, the ultrasonic treatment time is 12min, the heating refers to heating to 220°C, and the stirring time is 13min.

[0044] In the step A3, the mass ratio of mixture a to mixture b is 180:45, and the drying temperature is 80°C.

[0045] Comparative Example 1: Based on Example 2, a modified plastic masterbatch is provided, which comprises the following raw materials: a carrier resin, sepiolite fiber, lignin fiber and modified glass fiber, wherein the carrier resin is composed of polyethylene, random polypropylene and polypropylene in a mass ratio of 1:1.5:2.

[0046] The preparation method of the modified glass fiber is as follows: glass fiber is mixed with anhydrous ethanol and subjected to ultrasonic treatment, vinyl triethoxysilane is added, the mixture is heated and stirred, and then cooled to room temperature, centrifuged to obtain a solid, and vacuum dried to obtain the modified glass fiber.

[0047] The ratio of the glass fiber, anhydrous ethanol and vinyl triethoxysilane is 13g:110mL:4g, the ultrasonic treatment time is 25min, the heating refers to heating to 55°C, and the vacuum drying time and temperature are 35min and 75°C respectively.

[0048] A method for preparing a modified plastic masterbatch, the method comprising the following steps: A1: Add the carrier resin into a high-speed mixer, heat it, and mix it at high speed to form a mixture a; A2: lignin fiber is added to anhydrous ethanol and ultrasonically treated, and then added to a high-speed mixer, and sepiolite fiber and modified glass fiber are continuously added to the high-speed mixer and heated and stirred to obtain a mixture b; A3: Add mixed material a and mixed material b into a twin-screw extruder for blending and extrusion, pelletize, and dry to obtain a modified plastic masterbatch.

[0049] The heating temperature and time in step A1 are 265° C. and 11 min respectively, and the rotation speed of the high-speed mixing is 1900 r / min.

[0050] In the step A2, the ratio of lignin fiber, anhydrous ethanol, sepiolite fiber and modified glass fiber is 13g:60mL:6g:6g, the ultrasonic treatment time is 10min, the heating refers to heating to 215°C, and the stirring time is 12min.

[0051] In the step A3, the mass ratio of mixture a to mixture b is 165:38, and the drying temperature is 75°C.

[0052] Comparative Example 2: Based on Example 2, the sepiolite fiber in the raw material was removed and replaced with modified lignin fiber of equal mass. Other conditions were consistent with Example 2.

[0053] Comparative Example 3: Based on Example 2, the modified lignin fiber in the raw material was removed and replaced with sepiolite fiber of equal mass. Other conditions were consistent with Example 2.

[0054] Comparative Example 4: Based on Example 2, the modified glass fiber in the raw material was removed and replaced with modified lignin fiber of equal mass. Other conditions were consistent with Example 2.

[0055] Performance test: Flame retardant performance determination: The plastic masterbatch obtained in Examples 1-3 and Comparative Examples 1-4 was used as a sample, and a specimen was made into a spline according to the national standard GB / T 1040-2008. The spline was tested for flame retardancy with reference to the national standard GB / T 2406-2008. In addition, the heat resistance of Examples 1-3, Comparative Example 2 and Comparative Example 4 was tested with reference to the national standard GB / T 1634-2019. The above test results are shown in Table 1.

[0056] Table 1 Flame retardant and heat resistance test results of different plastic masterbatch samples Sample Limiting oxygen index% Heat deformation temperature℃ Example 1 33.7 234.2 Example 2 33.4 231.4 Example 3 32.7 236.0 Comparative Example 1 26.4 - Comparative Example 2 25.8 180.3 Comparative Example 3 22.1 - Comparative Example 4 26.1 203.6 It can be concluded from Table 1 that the limiting oxygen index of Examples 1-3 is greater than that of Comparative Examples 1-4, and the heat deformation temperature is also greater than that of Comparative Examples 2 and 4. In Comparative Example 1, the lignin fiber was not modified, and the nitrogen content of the lignin fiber was less than that of the modified lignin fiber, which reduced the generation of nitrogen, and thus the flame retardant effect of the plastic masterbatch decreased; in Comparative Examples 2-4, any one of the modified lignin fiber, sepiolite fiber and modified glass fiber was missing, and the flame retardant performance of the plastic masterbatch was reduced. The modified lignin fiber, sepiolite fiber and modified glass fiber can improve the flame retardant performance of the modified masterbatch from three dimensions: gas flame retardancy, heat absorption and structural stability. The modified lignin fiber forms a stable carbon layer at high temperature, and the modified lignin fiber generated by nitrogen is matched with the sepiolite fiber to absorb a large amount of heat, thereby reducing the overall temperature; in addition, the addition of the modified glass fiber itself is non-flammable, and the formed skeleton remains stable at high temperature, preventing the disintegration of the material. In Comparative Example 2, due to the lack of the presence of sepiolite fiber, the heat cannot be absorbed and the softening temperature of the plastic masterbatch is reduced. In Comparative Example 4, due to the lack of modified glass fiber, there is no skeleton support, and the softening temperature of the plastic masterbatch is also reduced.

[0057] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.

Claims

1. A modified plastic masterbatch, characterized in that: The modified plastic masterbatch comprises the following raw materials: carrier resin, sepiolite fiber, modified lignin fiber and modified glass fiber, wherein the carrier resin is composed of polyethylene, random polypropylene and polypropylene in a mass ratio of 1:1-2:1-3, and the preparation method of the modified lignin fiber comprises the following steps: (1) dissolving lignin in an alkaline solution, then adding formaldehyde and mixing, and then heating to obtain a mixture; (2) Add melamine to the mixture and keep it warm, then add dilute hydrochloric acid and stir, let it stand to form a precipitate, filter it, wash the solid with distilled water, and dry it to obtain the modified lignin fiber.

2. A modified plastic masterbatch according to claim 1, characterized in that: In the step (1), the ratio of lignin, alkaline solution and formaldehyde is 4-6g:100-150mL:2-5mL, wherein the alkaline solution refers to a sodium hydroxide solution with a mass fraction of 1-5%, and the heating time and temperature are 1-2h and 70-80°C, respectively.

3. A modified plastic masterbatch according to claim 1, characterized in that: In the step (2), the ratio of the mixture, melamine and dilute hydrochloric acid is 150-180 mL: 2-6 g: 10-15 mL, wherein the mass fraction of the dilute hydrochloric acid is 35-38%, and the drying time and temperature are 1-2 h and 80-100° C., respectively.

4. The modified plastic masterbatch according to claim 1, characterized in that: The preparation method of the modified glass fiber is as follows: glass fiber is mixed with anhydrous ethanol and subjected to ultrasonic treatment, vinyl triethoxysilane is added, the mixture is heated and stirred, and then cooled to room temperature, centrifuged to obtain a solid, and vacuum dried to obtain the modified glass fiber.

5. A modified plastic masterbatch according to claim 4, characterized in that: The ratio of the glass fiber, anhydrous ethanol and vinyl triethoxysilane is 10-15g:100-120mL:2-5g, the ultrasonic treatment time is 20-30min, the heating refers to heating to 50-60°C, and the vacuum drying time and temperature are 30-40min and 70-80°C respectively.

6. A method for preparing a modified plastic masterbatch as claimed in claim 1, characterized in that: Preparation method of modified plastic masterbatch The following steps are involved: A1: Add the carrier resin into a high-speed mixer, heat it, and mix it at high speed to form a mixture a; A2: The modified lignin fiber is added to anhydrous ethanol and ultrasonically treated, and then added to a high-speed mixer, and sepiolite fiber and modified glass fiber are continuously added to the high-speed mixer and heated and stirred to obtain a mixture b; A3: Add mixed material a and mixed material b into a twin-screw extruder for blending and extrusion, pelletize, and dry to obtain a modified plastic masterbatch.

7. The method for preparing a modified plastic masterbatch according to claim 6, characterized in that: The heating temperature and time in step A1 are 260-270° C. and 10-12 min respectively, and the rotation speed of the high-speed mixing is 1800-2000 r / min.

8. The method for preparing a modified plastic masterbatch according to claim 6, characterized in that: In the step A2, the ratio of modified lignin fiber, anhydrous ethanol, sepiolite fiber and modified glass fiber is 10-15g:50-70mL:5-7g:5-8g, the ultrasonic treatment time is 8-12min, the heating refers to heating to 210-220°C, and the stirring time is 12-13min.

9. The method for preparing a modified plastic masterbatch according to claim 6, characterized in that: In the step A3, the mass ratio of the mixture a to the mixture b is 150-180:30-45, and the drying temperature is 70-80°C.

Citation Information

Patent Citations

  • Preparation method for solvent-based lignin-cyanamide derivative flame retardant

    CN102250360A

  • Composite masterbatch of mineral fiber with high length-diameter ratio and preparation method

    CN102604200A

  • Plastic masterbatch and preparation method thereof

    CN111534002A

  • Lignin-based polyurethane film and preparation method thereof

    CN112724430A

  • Meltable lignin compositions, method for producing them and their uses

    US20210040273A1